Inflation Surprises in a New Keynesian Economy with a True Consumption Function - Roberto Tamborini (Center for Economic Studies and ifo Institute (CESifo), 2022)
The resurgence of inflation since the late 2021 is now accompanied by a reversal of prospects of growth, reviving fears of stagflation across the world (IMF 2022, World Bank 2022). In almost all accounts of the mounting stagflation threats a prominent role is played by the fall of households' purchasing power, and hence consumption, owing to the inflation shock visà-vis nominal wages lagging behind. The theoretical issue that motivates this paper is that this endogenous real income effect of inflation surprises, independent of restrictive monetary policy, is not present in the standard New Keynesian models for monetary policy. The paper shows how this channel can be introduced reformulating the consumption function, with the consequence that it exerts a stabilisation effect on inflation endogenously. By means of simulations the paper discusses the main monetary policy implication: what is the role left to monetary policy which purports to curb inflation in the same way?
Keywords: E17; E30; E50; 330; cost-push inflation; real income effect; stagflation; New Keynesian models for monetary policy